Preparation of Nanocomposite Biopolymer Films from Commelina coelestis Willd Starch and Their Nanostructures as a Potential Replacement for Single-Use Polymers - Lucia García-Guzmán; Gonzalo Velazquez; Israel Arzate-Vázquez; Patricia Castaño-Rivera; Maria Guerra-Valle; Johanna Castaño; Andrea Y. Guadarrama-Lezama (Foods)
This study explored the effect of incorporating cellulose and starch nanoparticles, obtained from the Commelina coelestis Willd plant, on the physical and chemical properties of starch-based films derived from the same plant. Additionally, the synergistic effect of combining the nanostructures was assessed. The nanocomposite biopolymer films were prepared by the casting method using 1 and 3 wt% concentrations of the nanostructures (CNCs: cellulose nanocrystals, CNFs: cellulose nanofibers, SNCs: starch nanocrystals), or their blend. The physicochemical (swelling capacity and water solubility), morphological (SEM and AFM), thermal (DSC and TGA), and mechanical properties (tensile strength, elongation at break, and Young’s modulus) of the films were evaluated. The nanocomposite biopolymer films exhibited better dimensional stability (40–60%) than the control films. Tensile strength (8–300%) and Young’s modulus (15–690%) were improved. Moreover, these films displayed enhanced thermal stability, withstanding temperatures exceeding 305 °C. FTIR spectra evidenced intermolecular interaction among the matrix and nanostructures. Microscopic analyses further supported the integrity of the films, which displayed a homogeneous surface and the absence of fractures. In addition, the nanocomposite biopolymer films prepared with 1 wt% cellulose nanocrystals and nanofibers had a lower opacity than those with a higher percentage (3 wt%). Overall, our findings suggest that the Commelina coelestis Willd is a promising starch source that can be used to obtain nanocomposite biopolymer films as an alternative to produce novel, efficient, and eco-friendly materials with adequate thermo-mechanical properties intended to replace conventional plastic materials in single-use applications such as those used in the food packaging industry.